Enhancing Learning Processes: The Impact of Guidance and Counseling Programs on Visually Impaired High School Students - Yuwono, Imam; Utomo (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
This study examines the role and effect of a guidance and counseling program on the learning processes of visually impaired students within an inclusive educational environment. The study investigates the implementation of principles and services offered by the program to address the specific needs of visually impaired students. The study was conducted in several senior high schools that provide inclusive education in Bandung and its surrounding areas. The study employs a combination of quantitative and qualitative approaches to align with the characteristics of the challenges faced by visually impaired students. The findings reveal various difficulties visually impaired students encounter during their learning processes. In response, teachers and counselors provide guidance and counseling interventions to support students in overcoming these challenges. The programs implemented address the immediate educational obstacles and foster students’ self-confidence, encouraging their pursuit of higher education opportunities, such as entering university. This study contributes to the body of knowledge by shedding light on the significance of guidance and counseling programs tailored to visually impaired high school students’ unique needs. The findings underscore the importance of incorporating comprehensive support systems within inclusive educational settings to enhance visually impaired students’ learning experiences and outcomes. The study’s implications highlight the potential for further research and the need for policymakers and educational institutions to prioritize developing and implementing effective guidance and counseling programs for visually impaired students.